Effect of HBV-HDV co-infection on HBV-HCC co-recurrence in patients - Baskiran, A; Akbulut, S; Sahin, TT; Koc, C; Karakas, S; Ince, V; Yurdaydin, C; Yilmaz, S (2020)
Purpose To evaluate the effect of hepatitis D virus (HDV) on hepatitis B virus-hepatocellular carcinoma (HBV-HCC) co-recurrence in patients undergoing living donor liver transplantation (LDLT) for HBV alone or HBV-HDV coinfection. Methods Between 2002 and 2019, 254 HBV-HCC patients underwent LDLT. The patients were divided into two groups after the application of the exclusion criteria: HBV-HCC (Group B;n = 163) and HBV-HDV-HCC (Group D;n = 31). First, the B and D groups were compared in terms of demographic and clinical parameters. Second, patients with (n = 16) and without (n = 178) post-transplant HBV-HCC co-recurrences were grouped and compared in terms of the same parameters. Results Although the risk of HBV-HCC co-recurrence in group D was 4.99-fold higher than in group B, the risk of HBV recurrence alone in group D was 12.5-fold lower than in group B. The AFP (OR = 4.4), Milan criteria (beyond; OR = 18.8), and HDV (OR = 8.1) were identified as the independent risk factors affecting post-transplant HBV-HCC co-recurrence. The Milan criteria (OR = 2.1) and HBV-HCC co-recurrence (OR = 10.9) were identified as the risk factors affecting post-transplant mortality. HBV-HCC co-recurrence developed in 26.5% of patients in Group B and 100% in Group D (OR = 40;p = 0.001). HCC recurrence alone developed in 10% of patients without HBV recurrence in group B and 0% of patients without HBV recurrence in group D (OR = 5.7). Conclusion This study showed that the risk of HBV recurrence alone was reduced by 12.5-fold in the presence of HDV; however, the HCC recurrence occurred in all patients with HDV when HBV recurrence developed. C1 [Baskiran, Adil; Akbulut, Sami; Sahin, Tevfik Tolga; Koc, Cemalettin; Karakas, Serdar; Ince, Volkan; Yilmaz, Sezai] Inonu Univ, Fac Med, Liver Transplant Inst, Dept Surg, Elazig Yolu 10 Km, TR-44280 Malatya, Turkey. [Yurdaydin, Cihan] Koc Univ, Fac Med, Dept Gastroenterol, TR-34450 Istanbul, Turkey.